2011
DOI: 10.1039/c0dt01569e
|View full text |Cite
|
Sign up to set email alerts
|

Metal-mediated aggregation of DNA comprising 2,2′-bipyridine nucleoside, an asymmetrically substituted chiral bidentate ligand

Abstract: The incorporation of an artificial 5-methyl-2,2'-bipyridine nucleoside at the 5' terminus of an otherwise self-complementary oligonucleotide sequence opens up the opportunity of metal-mediated aggregation of DNA double helices triggered by the addition of the respective metal ions. Interestingly, two-dimensional aggregates (DNA monolayers) are formed in the presence of nickel(ii), whereas copper(ii) leads to the formation of three-dimensional disc-shaped structures. With iron(ii), a coexistence of both types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
14
0
3
Order By: Relevance
“…Three complementary approaches have been published related to the formation of metal-stabilized three-way junctions.T he attachment of ab identate ligand such as 2,2'bipyridine at the terminus of as ingle-stranded oligonucleotide enables ametal-mediated DNAassembly in the presence of metal ions favoring an octahedral coordination geometry. [49] If this single-stranded oligonucleotide is self-complementary,t hen the resulting conjugate can aggregate through DNAd uplex formation, giving rise to metal-mediated 3WJs (Figure 6a). Depending on the experimental conditions,twodimensional and three-dimensional aggregates have been observed.…”
Section: Three-way Junctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three complementary approaches have been published related to the formation of metal-stabilized three-way junctions.T he attachment of ab identate ligand such as 2,2'bipyridine at the terminus of as ingle-stranded oligonucleotide enables ametal-mediated DNAassembly in the presence of metal ions favoring an octahedral coordination geometry. [49] If this single-stranded oligonucleotide is self-complementary,t hen the resulting conjugate can aggregate through DNAd uplex formation, giving rise to metal-mediated 3WJs (Figure 6a). Depending on the experimental conditions,twodimensional and three-dimensional aggregates have been observed.…”
Section: Three-way Junctionsmentioning
confidence: 99%
“…Depending on the experimental conditions,twodimensional and three-dimensional aggregates have been observed. [49] Alternatively,a na rtificial metal-modified 3WJ can be obtained by introducing a2 ,2'-bipyridine-containing nucleoside into the center of an otherwise regular DNA3 WJ Figure 5. Selected Ag I -mediated base triples.…”
Section: Three-way Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When attached to the 5′‐end of palindromic DNA oligonucleotides, 5Me Bipy nucleoside can be used to generate DNA‐metal aggregates in the presence of Fe 2+ , Ni 2+ and Cu 2+ 47. 48 Such conjugates can be considered a first step on the way towards metal‐containing DNA nanostructures.…”
Section: Metal‐mediated Base Pairs With Artificial Nucleosidesmentioning
confidence: 99%
“…While the naturally occurring pyrimidine nucleosides cytidine and thymidine are known to be capable of forming silver(I)-and mercury(II)-mediated base pairs, respectively, numerous artificial nucleosides have been developed for an application in metal-mediated base pairs. These include for example hydroxypyridone, [10] salen, [11] dipicolylamine, [12] 2,2'-bipyridine, [13] imidazole [14] and triazole. [15] In particular, the imidazole-Ag + -imidazole base pair has been intensively characterized (Scheme 1a): A comparison with other azole-based nucleosides indicated that it should form highly stable metal-mediated base pairs.…”
Section: Introductionmentioning
confidence: 99%